Anticancer effect of icaritin on prostate cancer via regulating miR‐381‐3p and its target gene UBE2C - Hu, Jimeng (Cancer Med, 2019)
Prostate cancer (PCa) is one of the most common health‐related issues in the male individuals of western countries. Icaritin (ICT) is a traditional Chinese herbal medicine that exhibits antitumor efficacy in variety of cancers including PCa. However, the precise function and detailed molecular mechanism of ICT in the regression of PCa remain unclear. Ubiquitin‐conjugating enzyme E2C (UBE2C) is an anaphase‐promoting complex/cyclosome (APC/C)‐specific ubiquitin conjugating enzyme, which acts as an oncogene in PCa progression. The function of ICT in PCa was investigated in transgenic adenocarcinoma mouse prostate (TRAMP) mice using survival analysis, hematoxylin and eosin (HE) staining, TUNEL assay, and immunohistochemistry and in human PCa cell lines using various molecular techniques and functional assays including plasmid construction and transfection. Bioinformatic analyses were performed to identify the interaction between miRNA and UBE2C via the TargetScan algorithm. We demonstrated that ICT inhibited the development and progression of PCa in TRAMP mice by improving the survival rate and tumor differentiation. Furthermore, we found that ICT could significantly inhibit cell proliferation and invasion and induce apoptosis in PCa cells. Consistently, downregulation of UBE2C suppressed the proliferation and invasion of PCa cells. Moreover, a luciferase reporter assay confirmed that UBE2C was a direct target of miR‐381‐3p. Meanwhile, ICT simultaneously downregulated UBE2C expression and upregulated miR‐381‐3p levels in human PCa cells. Altogether, our findings provide a strong rationale for the clinical application of ICT as a potential oncotherapeutic agent against PCa via a novel molecular mechanism of regulating the miR‐381‐3p/UBE2C pathway.